Case Study PAB Unit Trust Management Berhad - Mohd Noor, Ahmad Fathi (1998)
The Investment Committee lays out strict procedures as to the management of the trust funds. The committee stipulates that if any investment in KLSE goes down by more than 20% than the fund manager must take all necessary steps to force sell the counters and to recover the remaining balance. The fund managers are allowed only to purchase approved sectors and counters. They are definitely not allowed to purchase any shares or counters that are not approved for. As to other means of investment, as in derivative securities, prior approval is required before any decisions being made. Tan Sri Datuk Chang Min Tat is the only independent member in the committee. The Securities Commissions requires independent members to be at least 1/3 (onethird) of the total members. The independent member is supposed to represent interest of the public. Other members in the committee are directly related to the bank by way of employment. Currently Amanah Saham PHB (ASPHB) has no cash to invest in stock market since approximately 90% of total fund is already in the market. The ASPHB records an unrealized loss of RM50 million or 70% of total investment as at 30 April 1998.